Influence Tax Aggressiveness, Debt Policy and Financial Performance Against Company Value - Indawati, Indawati; Naily Happy Rizkiyani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The purpose of this study is to determine the influence of tax aggressiveness, debt policy, and financial performance on the value of companies in the property and real estate sector listed on the Indonesia Stock Exchange (IDX). The population of this study is property and real estate companies listed on the Indonesia Stock Exchange from 2018-2023. In this study, 72 samples from 12 companies were sampled using the purposive sampling method and observed for 6 years. In this study, the multiple linear regression analysis technique is used in the application of e-views 9. The results show that tax aggressiveness, debt policy, and financial performance have a simultaneous effect on the company's value. Tax aggressiveness has a positive effect on the company's value, as investors consider the extent to which a company complies with its tax obligations. Companies exhibiting high levels of tax aggressiveness are often perceived as riskier, prompting investors to exercise greater caution in their investment decisions. Debt has a positive effect on the company's value, as there is a strong relationship between the two. The more optimal the debt policy implemented by management, the more positively investors perceive the firm. A well-managed debt policy tends to enhance firm value by reflecting capital structure efficiency and the firm's ability to manage financial risk. Financial performance does not affect the company's value.